Increased individual chromosomal radiosensitivity of human lymphocytes as a parameter of cancer risk - Dyomina, E.A.; Ryabchenko, N.M. (Experimental Oncology, 2007)
Aim: Evaluation of chromosomal radiosensitivity of healthy individuals and determination those with the increased susceptibility to radiogenic cancer. Methods: Cytogenetic examination of radiation induced injuries in lymphocytes of healthy individuals (n = 103) was carried out on the basis of G2-assay. Test system of peripheral blood lymphocytes with metaphase analysis was used. Results: On the basis of the obtained “stage-effect” and “dose-effect” calibrating curves the scheme of cytogenetic examinations of healthy individuals was developed. Analysis of cytogenetic parameters induced by G2 irradiation at 1.5 Gy dose revealed their high interindividual variability. The highest differences were registered for chromatid type aberrations (CV = 42.1%) with the chromatid break predominance in the spectrum (CV = 37.5%). Statistical analysis of the distributions of the obtained individual cytogenetic parameters indicated 12% individuals with increased chromosomal radiosensitivity. Conclusions: Cytogenetic evaluation of individual chromosomal radiosensitivity based on G2-assay has its perspectives in the formation of groups with increased risk of radiogenic cancer developing and its primary prophylactics among healthy population. Цель: оценка радиочувствительности здоровых лиц на уровне хромосом лимфоцитов и определение индивидуумов с
повышенным риском радиоиндуцированных новообразований. Методы: цитогенетическое исследование радиационно
индуцированных поврежедений в лимфоцитах здоровых доноров (n = 103) проведено на основе G = 103) проведено на основе G2
-теста. Использована
тест-система лимфоцитов периферической крови с последующим метафазным анализом. Результаты: на основе построения
калибровочных кривых “стадия-эффект”, “доза-эффект” разработана схема цитогенетического обследования условно
здоровых лиц. Анализ величин цитогенетических показателей, полученных при облучении в G2
-периоде клеточного цикла
в дозе 1,5 Гр, выявил их значительную вариабельность. Наибольшая вариабельность наблюдалась для аберраций хроматидного
типа (CV = 42,1%), в спектре которых преобладали одиночные хроматидные разрывы (CV = 37,5%). Статистический
анализ распределений индивидуальных значений полученных показателей позволил выявить 12% лиц с повышенной
радиационной чувствительностью хромосом. Выводы: цитогенетическая оценка индивидуальной радиочувствительности
на хромосомном уровне, основанная на G2
-тесте, имеет перспективы применения при формировании групп повышенного
риска радиоиндуцированных злокачественных новообразований и их первичной профилактики среди населения.